PENGELOLAAN PERPUSTAKAAN DI MADRASAH ALIYAH NEGERI 3 KOTA PADANG - Ratnawita Ratnawita; Lindra Yani (Jurnal Imam Bonjol: Kajian Ilmu Informasi dan Perpustakaan, 2021)
The  purpose of  this  research is  to  describe:  1)  planning   of  school  library,  2) management of school library personnel, 3) information material management (collection) school library, 4 ) Budget  school library system, 5) building  and  layout of  school  library,  6) management problem  of  school  library,  7) ) the  efforts that have   been   done   to  overcome  school  library  management  problem  at  MAN 3 Padang City. This research is a qualitative research and  use case study research design. Techniques of collecting data using interviews, observation and documentation. The method of data validity uses source triangulation and  method triangulation. Using interactive data analytics techniques. The results of the researchare: 1) the planning  includes the initial planning  and establishment of each period  of a year, 2) personnel management is good  enough but needs to be added by the manager, so that  each manager is more  focused on the task and function of each,  3)   material  the   information  (collections)  possessed  already   meet  the minimum  standards set  out   in  Permendiknas  Number   24   Year  2007   About Facilities and  Infrastructure School  / Madrasah Public  Education, 4) In the  budget management  system  using  the  traditional  approach budgeting  so doMANated financial  planning  instead of activity  planning, 5) The library space is not  suitable with  the  ratio  amount of  students, 6)managemen problem of  school library  are library space  is not  in accordance with the  ratio   amount  of students  and   lees librarians,  7) The effort   to  overcome the managemen problem that  is by making  a reading park, reading area, reading corner  to overcome the managemen problrm  of library space. Has requested the addition of school librarians to overcome the lack of lees librarians at MAN 3 Padang City.